A Study on Thermal Comfort Performance in Shared Facility Multi-Purpose Hall (MPH), Pagoh Educational Hub - Samsul Kamar, Azhan; Roslan, Nurul Hidayah (Progress in Engineering Application and Technology, 2025)
Thermal comfort significantly affects students' productivity and health in university’s environment, particularly during examinations. This study focuses on evaluating thermal comfort in the Multi-Purpose Hall of the Shared Facility in Pagoh Educational Hub, addressing student complaints about excessively cold conditions during exams. The objectives of this study are to evaluate occupants' perception of thermal comfort and to assess the thermal conditions of the Multi-Purpose Hall.There were two method approach was employed, integrating physical measurements (air temperature, humidity, air velocity) with subjective data from questionnaires. Thermal comfort parameters were analyzed using tools like the CBE Thermal Comfort Tool and compared against MS 1525-2014 and ASHRAE Standard-55 guidelines. The results indicate that air temperature and air velocity are below the recommended standards, with respondents predominantly experiencing "cool" or "slightly cool" sensations. PMV and PPD values from physical measurements (0.1 and 5.7%) suggest higher comfort levels compared to subjective perceptions (-1.5 and 53%), highlighting discrepancies between measured data and occupant feedback. In conclusion, the Multi-Purpose Hall's thermal conditions are not fully aligned with comfort standards. To enhance thermal comfort, indoor temperatures should be adjusted to 23–26°C with relative humidity maintained between 40–60%, ensuring compliance with ASHRAE standards and occupant satisfaction.